'Middle Saxon' settlement and society - Wright, Duncan (Archaeologist), (Archaeopress archaeology., 2015)
Duncan Wright explores the experiences of rural communities who lived between the seventh and ninth centuries in central and eastern England. Combining archaeology with documentary, place-name and topographic evidence, he shows how the settlements in which people lived provide a unique insight into social, economic and political conditions in 'Middle Saxon' England.